PELAKSANAAN SISTEM SURVEILANS KESEHATAN HAJI DI DINAS KESEHATAN KOTA SURABAYA - Krisnita Dwi Jayanti (Jurnal Ilmu Kesehatan Masyarakat, 2017)
Indonesian’s Hajj pilgrims were mostly high-risk pilgrims. Information system and epidemiological surveillance aimed to obtain information that can be used as feedback for planning, controlling, monitoring and evaluation of health pilgrimage.This study aimed to describe the implementation of hajj health surveillance in Surabaya Health Office.This research used descriptive method with cross sectional design. Respondents were the officers of hajj health surveilance program in Surabaya Health office. Data sources were primary and secondary data.The result showed that the data collection component from of data at risk hajj as much as 1428 (67%), the highest number of pilgrims aged 50-59 years 763 (36%), the pilgrims at most women 1138 (54%), pregnancy tests with negative results of 640 (56%), and the congregation in the observation 1375 (65%) . The program used to process the data is hajj integrated health system (SISKOHATKES) system is online. Epidemiological information of all pilgrims who departed must be recorded 100%, the pilgrims were examined 3 months before leaving still reaches 73% that should be 80%. The output of Hajj Surveilance was disseminated to Public Health Centers at the end of hajj season through monthly meetings. Keywords : Surveillance, Health of hajj, implementation, Surabaya City